EXTERIOR COAT INFECTIONS: ANTHRAX, RABIES - Erkinov Ilkhom; Ibroximova Risqiya Usmonovna (Journal of new century innovations, 2023)
Abstract: This scientific article provides an analysis of infectious diseases and the scientific basis of their treatment, an analysis of diseases such as rabies and anthrax.